A Scoring System to Predict the Risk of Postoperative Complications After Laparoscopic Gastrectomy for Gastric Cancer Based on a Large-Scale Retrospective Study. Issue 17 (May 2015) - Huang, Chang-Ming; Tu, Ru-Hong; Lin, Jian-Xian; Zheng, Chao-Hui; Li, Ping; Xie, Jian-Wei; Wang, Jia-Bin; Lu, Jun; Chen, Qi-Yue; Cao, Long-Long; Lin, Mi
Abstract : Abstract: To investigate the risk factors for postoperative complications following laparoscopic gastrectomy (LG) for gastric cancer and to use the risk factors to develop a predictive scoring system. Few studies have been designed to develop scoring systems to predict complications after LG for gastric cancer. We analyzed records of 2170 patients who underwent a LG for gastric cancer. A logistic regression model was used to identify the determinant variables and develop a predictive score. There were 2170 patients, of whom 299 (13.8%) developed overall complications and 78 (3.6%) developed major complications. A multivariate analysis showed the following adverse risk factors for overall complications: age ≥65 years, body mass index (BMI) ≥ 28 kg/m 2, tumor with pyloric obstruction, tumor with bleeding, and intraoperative blood loss ≥75 mL; age ≥65 years, a Charlson comorbidity score ≥3, tumor with bleeding and intraoperative blood loss ≥75 mL were identified as independent risk factors for major complications. Based on these factors, the authors developed the following predictive score: low risk (no risk factors), intermediate risk (1 risk factor), and high risk (≥2 risk factors). The overall complication rates were 8.3%, 15.6%, and 29.9% for the low-, intermediate-, and high-risk categories, respectively ( P < 0.001); the major complication rates in the 3 respective groups were 1.2%, 4.7%, and 10.0% ( P < 0.001). This simple scoring system could accurately predict the risk of postoperative complications after LG for gastric cancer. The score might be helpful in the selection of risk-adapted interventions to improve surgical safety.